The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/mt.2016.36
|View full text |Cite
|
Sign up to set email alerts
|

Chop Deficiency Protects Mice Against Bleomycin-induced Pulmonary Fibrosis by Attenuating M2 Macrophage Production

Abstract: C/EBP homologous protein (Chop) has been shown to have altered expression in patients with idiopathic pulmonary fibrosis (IPF), but its exact role in IPF pathoaetiology has not been fully addressed. Studies conducted in patients with IPF and Chop(-/-) mice have dissected the role of Chop and endoplasmic reticulum (ER) stress in pulmonary fibrosis pathogenesis. The effect of Chop deficiency on macrophage polarization and related signalling pathways were investigated to identify the underlying mechanisms. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
166
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(169 citation statements)
references
References 39 publications
2
166
1
Order By: Relevance
“…ER stress develops in airway cells in this model and is exacerbated by viral infection, and the UPR has been associated with the differentiation status of macrophages, and intrinsic ER stress within macrophages also occurs 16, 71, 75, 83, 84, 85, 86…”
Section: Oxidative and Er Stress In Chronic Inflammatory And Mucopurumentioning
confidence: 88%
See 1 more Smart Citation
“…ER stress develops in airway cells in this model and is exacerbated by viral infection, and the UPR has been associated with the differentiation status of macrophages, and intrinsic ER stress within macrophages also occurs 16, 71, 75, 83, 84, 85, 86…”
Section: Oxidative and Er Stress In Chronic Inflammatory And Mucopurumentioning
confidence: 88%
“…). Evidence for ER stress in human respiratory epithelial cells, particularly in type II pneumocytes, includes high expression of CHOP,71 activation of ATF6, XBP1 and ATF4 14. Activation of the UPR has been found in both inherited and sporadic IPF and associated with viral infection 13.…”
Section: Oxidative and Er Stress In Chronic Inflammatory And Mucopurumentioning
confidence: 99%
“…Changes in proteostasis lead to an increase of nonfunctional proteins, accumulation of cytotoxic proteins, and/or aggregation of misfolded proteins. In IPF lungs, evidence of altered proteostasis has been found at different levels, including protein misfolding, markers of ER stress (99)(100)(101)(102), defective autophagy, and impaired proteasome activity (103,104) (Table 4). For instance, familial pulmonary fibrosis is associated with several mutations in surfactant A and C genes (105)(106)(107)(108).…”
Section: Cellular Perturbations In the Ipf Lungmentioning
confidence: 99%
“…Mutation of the COPA gene, which encodes a protein involved in Golgi-to-ER retrieval was found to cause autoimmune arthritis and pulmonary interstitial lung disease, but although UPR activation was detected in the lung epithelium the mutation caused a multisystem disorder of altered immune function [15]. In two separate studies, the UPR transcription factor CHOP has been identified as a potential driver of fibrosis [16,61]. Deletion of Chop in mice reduced alveolar epithelial apoptosis following bleomycin treatment, but in one of the studies adoptive transfer of wildtype macrophages restored normal levels of pulmonary fibrosis [16].…”
Section: Pulmonary Fibrosismentioning
confidence: 99%
“…In two separate studies, the UPR transcription factor CHOP has been identified as a potential driver of fibrosis [16,61]. Deletion of Chop in mice reduced alveolar epithelial apoptosis following bleomycin treatment, but in one of the studies adoptive transfer of wildtype macrophages restored normal levels of pulmonary fibrosis [16]. This suggests that modulation of the innate immune response by CHOP in the macrophage may play an important role, at least in the bleomycin model of fibrosis.…”
Section: Pulmonary Fibrosismentioning
confidence: 99%